(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This article looks into the impact of derivatives on capital market’s liquidity management, with regard to their benefits and risks. Market liquidity is further bolstered through the use of derived products – futures, options, and swaps – which attracts dyers participants, drive higher volumes and enable sound price discovery.